Generation of Mid‐Infrared Noise‐Like Pulses from a Polarization‐Maintaining Fluoride Fiber Oscillator - Linpeng Yu; Jinhui Liang; Ziya Tang; Qinghui Zeng; Jinzhang Wang; Jiachen Wang; Xing Luo; Peiguang Yan; Fanlong Dong; Xing Liu; Qitao Lue; Chunyu Guo; et al. (Advanced Photonics Research, 2023)
Noise‐like pulses (NLPs) are becoming increasingly attractive for a variety of applications such as supercontinuum generation, materials processing, and low‐coherence spectral interferometry. Related research in the near‐infrared region is extensive, yet few studies have been reported in the mid‐infrared (MIR) region. Herein, a systematic investigation of MIR NLPs is made for the first time. An approach is presented by exploiting a polarization‐maintaining fluoride fiber in the mode‐locked oscillator to cause a polarization‐dependent delay between the orthogonal‐polarized components of intracavity circulating pulses, thus generating a series of ultrashort pulses which will eventually form a stable wave packet, namely, NLP. Numerical simulations based on the extended coupled nonlinear Schrödinger equations predict the generation of NLPs, and reveal key aspects of the pulse evolution. Experiments yield linearly polarized NLPs at 2.8 μm with a maximum average power of 498 mW and a spike width of 4.3 ps, corresponding to a pulse energy of 12 nJ. The experimental results are in good agreement with the simulation results. This work constitutes a major step toward the development of MIR ultrafast fiber lasers with NLPs output.